The Influence of Government Policy on Tourism Public Relations - Pradini, Gagih; Awaloedin, Dipa Teruna; Utami, Putri Priscilla; Andini, Davi Ayu (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research focuses on the role of Public Relations (PR) in the tourism industry, specifically in the context of government policy influence. The study employs descriptive research to analyse the impact of government policies on PR functions and strategies within the tourism sector. Additionally, a SWOT analysis is conducted to assess the strengths, weaknesses, opportunities, and threats faced by the tourism industry in Indonesia. The findings highlight the importance of effective PR strategies in building and maintaining positive relationships with various stakeholders, including the government, the media, and the public. The research suggests that PR practitioners in the tourism sector should enhance issue management, crisis response, and adaptability to technological advancements. Furthermore, the study recommends improving communication effectiveness to benefit all stakeholders involved in tourism activities. Overall, the research contributes to understanding the intricate relationship between government policies, PR practices, and the sustainable development of the tourism industry.